Increased virtual resolution for sub-pixel displacement algorithm optimization in digital image correlation for AISI 1020 steel - Silmara M. Cardoso; Maurício M. Ribeiro; Douglas S. Silva; Raí Felipe P. Junio; Sergio N. Monteiro; Jean da S. Rodrigues (Journal of Materials Research and Technology)
The development of the digital image correlation (DIC) technique has required the use of cameras with increasingly higher resolution, as well as requiring complex sub-pixel tracking algorithms with exponentially increasing computational cost. This article proposes a DIC algorithm based on the correlation coefficient curve-fitting method, minimizing SSD or ZNSSD correlation criteria, with the help of increasing the virtual resolution of the images through bicubic interpolation, for obtain an accurate, robust and reliable algorithm according to the highest computational efficiency. The developed algorithm was virtually validated using synthetic images and experimentally using AISI 1020 steel samples test in tension, performed with strain gauges. The results showed a reduction in the error observed in synthetic images with increased magnification and good agreement with the deformation data obtained using the conventional extensometry technique.